Internalisasi Nilai-Nilai Pendidikan Menurut Abraham Maslow pada Kinerja Guru di MTSN 6 Sumedang - Sariah, Dedeh; Nugraha, Mulyawan Safwandy; Rukmana, Ratna (Jurnal Penelitian Ilmu Ushuluddin, 2025)
This study aims to fill the gap in the study of the relationship between Maslow's motivation theory and teacher performance, which has not been widely explored in the context of madrasah. The main problem identified was the low performance of teachers at MTs Negeri 6 Sumedang, such as the lack of use of varied learning media and innovative methods, as well as the lack of motivation to improve pedagogical quality. This study uses qualitative methods through interviews, observations, and documentation to assess the fulfillment of teacher needs based on Maslow's hierarchy. The results of the study show that the fulfillment of physiological needs and sense of security of ASN teachers is relatively good, but the need for appreciation and self-actualization still requires special attention. The awards given tend to be limited to verbal praise, while self-actualization is reflected in the teacher's participation in the training. Motivational strategies include the provision of performance-based incentives, periodic training, and formal recognition. A conducive work environment and transformational leadership also contribute significantly to teacher motivation. The application of Maslow's theory is able to improve teacher motivation and performance through a structured approach at each level of need. It is recommended that madrasah increase formal awards and provide more opportunities for professional development. This effort is expected to be able to create teachers who are more motivated, innovative, and contribute to the quality of education.